2018
DOI: 10.1186/s13014-018-1001-6
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic ablative radiotherapy for ultra-central lung tumors: prioritize target coverage or organs at risk?

Abstract: BackgroundLung stereotactic ablative radiotherapy (SABR) is associated with low morbidity, however there is an increased risk of treatment-related toxicity in tumors directly abutting or invading the proximal bronchial tree, termed ‘ultra-central’ tumors. As there is no consensus regarding the optimal radiotherapy treatment regimen for these tumors, we performed a modeling study to evaluate the trade-offs between predicted toxicity and local control for commonly used high-precision dose-fractionation regimens.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…The rate of grade 2 or 3 toxicity was 7.9% and no grade 4 or 5 toxicities were observed. Murrell et al 19 suggested that 60 Gy in eight fractions was practical. Table 5 summarizes several other studies on SBRT for ultracentral lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of grade 2 or 3 toxicity was 7.9% and no grade 4 or 5 toxicities were observed. Murrell et al 19 suggested that 60 Gy in eight fractions was practical. Table 5 summarizes several other studies on SBRT for ultracentral lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Organs at risk contouring was adopted from RTOG 0813, EORTC LungTech, SUNSET, and RTOG 1106 contouring atlas, and normal tissue constraints were adopted from RTOG 0813 and previous HILUS studies . Meanwhile, maximum point dose and volumetric maximum dose analyses were evaluated for OAR including esophagus, heart, pulmonary artery, pulmonary vein, spinal cord, ipsilateral lung, contralateral lung, lung total, trachea, mainstem bronchi, lobe bronchi, and proximal bronchial tree.…”
Section: Methodsmentioning
confidence: 99%
“…Organs at risk contouring was adopted from RTOG 0813, 35 EORTC LungTech, 36 SUNSET, 18 and RTOG 1106 contouring atlas, 37 and normal tissue constraints were adopted from RTOG 0813 and previous HILUS studies. 6,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Meanwhile, maximum point dose and volumetric maximum dose analyses were evaluated for OAR including esophagus, heart, pulmonary artery, pulmonary vein, spinal cord, ipsilateral lung, contralateral lung, lung total, trachea, mainstem bronchi, lobe bronchi, and proximal bronchial tree. Treated doses were converted to biologically effective doses (BED) based on the formula: nd [1 + d/(α/β)], where n is number of fractions, and d is dose/fraction (Gy); assuming α/β value of 10 for NSCLC (ie BED 10 ) and α/β value of 3 for normal tissues (ie BED 3 ).…”
Section: Organs At Risk Normal Tissue Constraints and Biologicallmentioning
confidence: 99%
See 2 more Smart Citations